Autobiographical memory in depression: state or trait marker? - Brittlebank, A; Scott, J; Williams, J; Ferrier, I (1993)
Two cognitive measures were used to assess 22 patients who met DSM-III-R criteria for major depressive disorder: the Autobiographical Memory (AM) test and the Dysfunctional Attitude Scale. They were followed up over seven months. Measurement of dysfunctional attitudes did not predict outcome at seven months. Overgeneral recall on the AM test at initial assessment, especially for emotionally positive memories, was highly correlated with failure to recover from depression and accounted for 33% of the variance in HRSD score at follow-up. Overgeneral recall of emotional memories did not change during follow-up. It is suggested that overgenerality is a trait marker indicating vulnerability to persistent depression.